Advances in the neurological and neurosurgical management of peripheral nerve trauma. Issue 2 (28th April 2015) - Simon, Neil G; Spinner, Robert J; Kline, David G; Kliot, Michel
Abstract : Peripheral nerve trauma frequently affects younger people and may result in significant and long-lasting functional disability. Currently, diagnosis and monitoring of peripheral nerve injury relies on clinical and electrodiagnostic information, supplemented by intraoperative electrophysiological studies. However, in a significant proportion of nerve injuries, the likelihood of spontaneous regeneration resulting in good functional outcome remains uncertain and unnecessary delays to treatment may be faced while monitoring for recovery. Advances in non-invasive imaging techniques to diagnose and monitor nerve injury and regeneration are being developed, and have the potential to streamline the decision-making process. In addition, advances in operative and non-operative treatment strategies may provide more effective ways to maximise functional outcomes following severe peripheral nerve trauma. This review discusses these advances in light of the current state of the art of management of peripheral nerve trauma.